Antiplatelet Therapy in Carotid Artery Stenting and Carotid Endarterectomy in the Asymptomatic Carotid Surgery Trial-2. Issue 3 (March 2016) - Huibers, A.; Halliday, A.; Bulbulia, R.; Coppi, G.; de Borst, G.J.; ,
Abstract : Objective: Strokes are infrequent but potentially serious complications following carotid intervention, but antiplatelet therapy can reduce these risks. There are currently no specific guidelines on dose or duration of peri-procedural antiplatelet treatment for patients undergoing carotid intervention. Within the ongoing Asymptomatic Carotid Surgery Trial-2 (ACST-2), this study aimed at assessing the current use of antiplatelet therapy before, during, and after CEA and CAS in patients with asymptomatic carotid stenosis. Methods: Questionnaires were sent to ACST-2 collaborators seeking information about the use of antiplatelet therapy during the pre-, peri-, and post-operative periods in patients undergoing carotid intervention at 77 participating sites and also whether sites tested for antiplatelet therapy resistance. Results: The response rate was 68/77 (88%). For CAS, 82% of sites used dual antiplatelet therapy (DAPT) pre-operatively and 86% post-operatively with a mean post-procedural duration of 3 months (range 1–12), while 9% continued DAPT life-long. For CEA only 31% used DAPT pre-operatively, 24% post-operatively with a mean post-procedural duration of 3 months (range 1–5), while 10% continued DAPT life-long. For those prescribing post-procedural mono antiplatelet (MAPT) therapy (76%), aspirin was more commonly prescribed (59%) than clopidogrel (6%) and 11% of centres did not show a preference for either aspirin or clopidogrel. Eleven centres (16%) tested for antiplatelet therapy resistance. Conclusion: There appears to be broad agreement on the use of antiplatelet therapy in ACST-2 patients undergoing carotid artery stenting and surgery. Although evidence to help guide the duration of peri-procedural antiplatelet therapy is limited, long-term treatment with DAPT appears similar between both treatment arms.